IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH DALAM RANGKA PEMBERDAYAAN SEKOLAH (STUDI KEBIJAKAN DI SEKOLAH DASAR DUA MEI CIPUTAT) - Mahyudin, Erta; Lestari, Ambar Sri (Universitas Nurul Jadid, 2021)
The purpose of this research is to obtain intensive and comprehensive description about the implementation of School Based Management for school empowering through optimization of management functions. This research applied qualitative approach, with descriptive method. The result showed that; (a) Education Foundation Dua Mei stays in dilemmatic position between giving full authority and keeping total stability, (b) School transparency and accountability to public doesn't run maximum because of public education level is inadequate, (c) Headmaster becomes empowered because he can empower hisself and his staff and teachers, (d) Teacher empowering results professional and autonomous teacher, and (e) The end target of school empowering is the improvement of instructional quality.